Mathematic Learning Media with a Split Attention Effect Perpective to Improve Multi-Representasi for Middle School Students - Marheinna, Adinda; Nizaruddin, Nizaruddin; Murtianto, Yanuar Hery (JPMI (Jurnal Pendidikan Matematika Indonesia), 2025)
In mathematics learning, students often experience difficulties that result in low student representation, teachers make learning innovations by developing media that can improve student representation in mathematics learning. This study aims to develop learning media from the perspective of the split attention effect to improve the multi-representation of junior high school students on the Pythagorean theorem material with feasible, practical and effective criteria. This study uses a research and development method that refers to the ADDIE model which consists of five phases, namely Analyze, Design, Develop, Implement, Evaluate. The subjects of the study were grade VIII students at one of the junior high schools in Semarang City. The results of the study obtained were the results of media expert validation on the Intrinsic Cognitive Load aspect of 93.34%, the Extraneous Cognitive Load aspect of 95.00%, the Germane Cognitive Load aspect of 88.00%, and material experts on the Intrinsic Cognitive Load aspect of 95.56%, the Extraneous Cognitive Load aspect of 82.23%, the Germane Cognitive Load aspect of 93.34% with the category of feasible to use. The results of the student response questionnaire in experimental class 1 percentage of 71% and experimental class 2 percentage of 75.8% with the practical category used. While the post-ANOVA test (Scheffe' test) showed that there was a significant difference in student representation before and after the application of split attention effect learning media obtained a mean difference of 1.8333 and a sig value of 0.740 or sig> 0.05. There was an increase in representation based on the N-Gain test in experimental class 1 of 67.06% and experimental class 2 of 70.32%, this shows that split attention effect learning media is effective in mathematics learning. Thus, this study can provide innovation in the teaching and learning process to meet student needs with split attention effect learning media as an effective strategy to improve student representation in learning mathematicsMedia Pembelajaran Matematika Dengan Perspektif Split Attention Effect Untuk Meningkatkan Multi Representasi Siswa SMPABSTRAKDalam pembelajaran matematika siswa sering mengalami kesulitan yang mengakibatkan representasi siswa rendah, guru membuat inovasi pembelajaran dengan pengembangan media yang dapat memingkatkan representasi siswa dalam pembelajaran matematika. Penelitian ini bertujuan mengembangkan media pembelajaran dari perspektif split attention effect untuk meningkatkan multi representasi siswa SMP pada materi teorema pythagoras dengan kriteria layak, praktis dan efektif. Studi ini menggunakan metode penelitian dan pengembangan yang mengacu pada model ADDIE yang terdiri dari lima fase yaitu Analyze, Design, Develop, Implement, Evaluate. Subjek penelitian ialah siswa kelas VIII disalah satu SMP Kota Semarang. Hasil penelitian yang diperoleh yaitu hasil validasi ahli media terhadap aspek Intrinsic Cognitive Load sebesar 93,34%, aspek Extraneous Cognitive Load sebesar 95,00%, aspek Germane Cognitive Load sebesar 88,00%, dan ahli materi pada aspek Intrinsic Cognitive Load sebesar 95,56%, aspek Extraneous Cognitive Load sebesar 82,23%, aspek Germane Cognitive Load sebesar 93,34% dengan kategori layak digunakan. Hasil angket respon siswa pada kelas eksperimen 1 persentase 71% dan kelas eksperimen 2 persentase 75,8% dengan kategori praktis digunakan. Sedangkan uji pasca anova (uji scheffe') menunjukkan bahwa adanya perbedaan secara signifikan pada representasi siswa sebelum dan sesudah penerapan media pembelajaran split attention effect yang diperoleh hasil mean difference sebesar 1.8333 dan nilai sig 0.740 atau sig > 0.05. Terjadi peningkatan representasi berdasarkan uji N-Gain pada kelas eksperimen 1 sebesar 67,06% dan kelas eksperimen 2 sebesar 70,32%, hal ini menunjukkan bahwa media pembelajaran split attention effect efektif digunakan dalam pembelajaran matematika. Dengan demikian, penelitian ini dapat memberikan inovasi dalam proses belajar mengajar guna memenuhi kebutuhan siswa dengan media pembelajaran split attention effect sebagai strategi yang efektif untuk meningkatkan representasi siswa dalam belajar matematika.Kata Kunci :Media Pembelajaran; Multi Representasi